Economic well-being, social mobility, and preferences for income redistribution: Evidence from a discrete choice experiment - Ilja Neustadt; Peter Zweifel (University of Zurich, Socioeconomic Institute, 2010)
In this paper, preferences for income redistribution in Switzerland are elicited through a Discrete Choice Experiment (DCE) performed in 2008. In addition to the amount of redistribution as a share of GDP, attributes also included its uses (working poor, the unemployed, old-age pensioners, families with children, people in ill health) and nationality of beneficiary (Swiss, Western European, others). Willingness to pay for redistribution increases with income and education, contradicting the conventional Meltzer-Richard (1981) model. The Prospect of Upward Mobility hypothesis [Hirschman and Rothschild (1973); Benabou and Ok (2001)] receives partial empirical support.
Keywords: C35; C93; D63; H29; 330; income redistribution; preferences; willingness to pay; discrete choice experiments; stated choice; economic well-being; social mobility; Einkommensverteilung; Soziale Wohlfahrtsfunktion; Willingness to pay; Diskrete Entscheidung; Lebensqualität; Soziale Mobilität; Schweiz